2022
DOI: 10.3389/fmars.2022.822978
|View full text |Cite
|
Sign up to set email alerts
|

Declining Pre-bloom Calanus finmarchicus Egg Production Adjacent to Two Major Overwintering Regions in the Northeastern Atlantic

Abstract: Calanus finmarchicus is a key secondary producer in the North Atlantic. Shortly prior to the spring bloom the animals ascend from diapause at depth to surface waters, where the females spawn partly, based on winter lipid reserves. C. finmarchicus eggs are an important prey of first feeding fish larvae inhabiting North Atlantic shelves during early spring and are thus essential for larval survival. Comprehensive late April surveys have been carried out on and around the Faroe shelf, which is located between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have suggested that the production and abundance of C. finmarchicus eggs is relatively high in the Faroe area (Stenevik et al 2007), indicating that newly spawned Faroe Plateau cod larvae in most cases have sufficient food resources during the first feeding period. However, phenological changes resulting in earlier emergence of C. finmarchicus have been observed in and around the Faroe area after the gut content study was conducted (Kristiansen et al 2016;Jacobsen et al 2018), and recent research has revealed that there has been a marked decline in C. finmarchicus pre-bloom egg production on the Faroe shelf after 2007 (Jacobsen et al 2022). Thus the feeding conditions of first-feeding cod larvae might have changed in recent years.…”
Section: Feeding Conditions During the Pre-bloom In Aprilmentioning
confidence: 99%
“…Previous studies have suggested that the production and abundance of C. finmarchicus eggs is relatively high in the Faroe area (Stenevik et al 2007), indicating that newly spawned Faroe Plateau cod larvae in most cases have sufficient food resources during the first feeding period. However, phenological changes resulting in earlier emergence of C. finmarchicus have been observed in and around the Faroe area after the gut content study was conducted (Kristiansen et al 2016;Jacobsen et al 2018), and recent research has revealed that there has been a marked decline in C. finmarchicus pre-bloom egg production on the Faroe shelf after 2007 (Jacobsen et al 2022). Thus the feeding conditions of first-feeding cod larvae might have changed in recent years.…”
Section: Feeding Conditions During the Pre-bloom In Aprilmentioning
confidence: 99%